OFR-115(1)-76 Technical And Economic Study Of The Modified In Situ Process For Oil Shale - Vol. I Investigation And Results - James L. Ash (The National Institute for Occupational Safety and Health (NIOSH), 1976)
This report contains the results of a technical and economic evaluation of conceptual systems for the underground mining, rubblization, and in situ retorting of deep oil shale deposits. Study efforts were first directed towards evaluation of the applicable geology, associated minerals, rock mechanics, in situ retorting, access mining, ventilation, rubblization, safety, and environmental impact factors. Conceptual systems were synthesized and then evaluated against these factors from both a technical and limited economic viewpoint. The results of these evaluations were then analyzed and, based upon this analysis, the following two systems were selected for further study: System II: Room and Pillar-Vertical Drill and Blast System IV: Tunnel Boring-Horizontal Ring Drill and Blast Due to the large number of variables to be considered, a computer program was developed and utilized to provide data for the cost trade-off studies and economic analysis. Results of the early computer runs indicated the value of the tool available? in the computer program and led to an extension in the contract to determine the sensitivity of the systems to several of the more apparent significant variables. These results in turn led to a refinement in the design assumptions and a better understanding of the technical and economic options available to an owner-operator of a Vertical Modified In Situ Shale Oil Extraction System. This report is submitted in fulfillment of the requirements of Contract Number 50241073 by Fenix & Scisson, Inc. to the Denver Mining Research Center, United States Department of the Interior, Bureau of Mines. Work was completed as of November, 1976.